Militarising music and demilitarising the military: making sense of “musoja” in Zimdancehall music - Mpofu, Phillip; Tembo, Charles (Taylor & Francis (Routledge), 2016)
The debate in this paper is enthused by the neurotic recurrence of the Shona linguistic expression “Musoja” (soldier) in Zimdancehall musical discourses. The enthusiastic utilisation of this name by the assemblage of Zimdancehall artists such as Sniper Storm, Jah Prayzer and Guspy Warrior, among others, is profoundly sustained by the militarised lingo, images and discourses that suffuse into their titles, chants, mannerisms, gesticulation and regalia in musical videos and performances. This article critically interrogates the foundation and motivations of the obsessive utilisation of the name “Musoja” (soldier) and other related militaristic expressions in the Zimdancehall music fraternity. It further analyses the outcomes and implications of employing these military images in expressing non-military phenomena as observed in Zimdancehall music to the image of the musicians, the content of music, their musical performances, music brand in general as well as the military service personnel. In addressing these issues, we make use of the discourse analysis method, semiotics and the theories of representation. It is argued in this paper that this militarisation of Zimdancehall music, where the artists symbolically present themselves as “soldiers” in music, is a way of transferring the power from the real soldiers to the seemingly feeble Zimdancehall musicians as a way of raising their own significance and the value of their music in a well-established music industry in Zimbabwe. Their militarised musical discourse has also resulted in militarisation of life by elevating military prowess above everything in life events. More so, it is ironic to note that the militarisation of Zimdancehall music has also resulted in the demilitarisation of the military service.